Kualitas Pelayanan Perizinan di Unit Pelayanan Terpadu Satu Atap (UPTSA) Kota Surabaya - Astuti, Wahyu Dwi; Sukristyanto, Agus; Indartuti, Endang (JPAP: Jurnal Penelitian Administrasi Publik, 2019)
The implementation of public facilities is the one of main function in the government implementation which is being obligation of government apparatus. One form of public service is giving permit service and also incorporate corporation in order to the corporate which has done get confession and legally from government. It is keep away from problem which can interrupt develop business in the other day. The aim from this observatory is to descript and how the SIUP allow service quality in UPTSA Surabaya city. In this thesis writing, use qualitative method where this observation use qualitative descriptive data. Based on observation from these research the concluding that quality of permit service that given by UPTSA officer Surabaya city to the people or the petitioner was good enough, however a success from UPTSA officer at present permit service, yet there the people or petitioner which is complain about facilities where was available and the time needed of service completion. More better ifUPTSA officer can adding extra support facilities, such as increasing parking field and keep toilet clean. So with adding that facilities can obtained service which was given by UPTSA truly satisfied the people or petitor is so much better to see the regulations first to prevent longer in time or help the completed documents can be process immediately by UPTSA officer.Â Keywords: service quality, public service, permit service